Tingkat Laju Korosi Atmosferik Baja Konstruksi di Lingkungan Pabrik Kelapa Sawit - Herdi Susanto; Joli Supardi; Sulaiman Ali (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
Environmental pollution that can cause atmospheric corrosion is the exhaust gas (exhaust fumes) generated from operating the palm oil industry. This atmospheric corrosion will reduce the volume and material mass of a machine component, so that if it reaches certain conditions the strength of the material will result in failure of industrial machine components. The corrosion rate of the construction steel can be measured using the weight loss method according to the ASTM G-50 standard and the ASTM G-1 standard. The research was conducted for one year and data collection was taken every month, the research location was at PT Agro Sinergi Nusantara Batee Puteh. The results of the study, the highest corrosion rate occurred in strip steel reaching 0.57 mpy in October and the lowest corrosion rate occurred for angled steel in September and cylindrical steel in May with a corrosion rate of 0.06 mpy. Keywords— atmospheric corrosion, palm oil industry, ASTM G-50, ASTM G-1, corrosion rate